IMPROVING STUDENTS SPEAKING SKILL AT SMAN 1 SOE KABUPATEN TIMUR TENGAH SELATAN (TTS) NUSA TENGGARA TIMUR IN EXPRESSING SIMPLE PRESENT THROUGH DESCRIBING PICTURE - Liunokas Yanpitherszon (Institut Agama Islam Negeri Palopo, 2018)
The objective of this research was to find out whether the use of describing picture activity effective or not to improve the students speaking skill at the SMAN 1 Soe Kabupaten Timur Tengah Selatan (TTS). This research employed pre experimental design. The population of this research was the students of SMAN 1 Soe Kabupaten Timur Tengah Selatan (TTS) The sample of the class was 20 students. The research data was collected by using speaking test to get the students speaking achievement, which was analyzed by inferential statistic through SPSS version 20.0 for windows program. The students result of posttest of pre experimental class is significantly improved than the students result of pretest by the mean score 68.00 > 50.10. The difference of both scores is statistically significant based on the t-test value at significant level 0.05 in which the probability value is lower than the significant level (0.00 < 0.05). So, H1 was accepted and H0 was rejected. It can be concluded that the use of describing picture effective to improve the students speaking skill. .